2017
DOI: 10.1037/rel0000068
|View full text |Cite
|
Sign up to set email alerts
|

The implications of workplace spirituality for person–environment fit theory.

Abstract: Person–environment (PE) fit theory is based on the premise that people flourish in work settings that are compatible with their skills, interests, values, and other characteristics. While the premise of PE fit theory appears to be straightforward, it is actually a complex and evolving framework with much left to be understood about what exactly “fit” encompasses and how it relates to human behavior and organizational outcomes. In contrast to the vast literature on PE fit theory, which dates back more than 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 63 publications
(149 reference statements)
3
60
0
2
Order By: Relevance
“…Together, these three features shape the degree of compatibility or congruence between religious identity and the workplace. Borrowing from the notion of person‐environment fit (Milliman et al, ), we argue congruence can be viewed as the relationship between two or more identities activated at the same time. In the context of religious identity in the workplace, we find that congruence reflects a continuum varying in its degree, ranging from the identity states of incongruence (e.g., in conflict or tension) to coexistence (e.g., as separate with neither synergy nor conflict) to high congruence (e.g., fit, compatible, or synergistic).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Together, these three features shape the degree of compatibility or congruence between religious identity and the workplace. Borrowing from the notion of person‐environment fit (Milliman et al, ), we argue congruence can be viewed as the relationship between two or more identities activated at the same time. In the context of religious identity in the workplace, we find that congruence reflects a continuum varying in its degree, ranging from the identity states of incongruence (e.g., in conflict or tension) to coexistence (e.g., as separate with neither synergy nor conflict) to high congruence (e.g., fit, compatible, or synergistic).…”
Section: Resultsmentioning
confidence: 99%
“…Together, these three features shape the degree of compatibility or congruence between religious identity and the workplace. Borrowing from the notion of person-environment fit (Milliman et al, 2017), we argue congruence can be viewed as the relationship between two…”
Section: A Religion's System Of Belief Norms and Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Extended research in the field of psychology has shown that spirituality tends to promote adaptability, task commitment, , wellness, profitability and personal fulfilment (12). Consequentially, spirited teachers would be represented as a "whole person" at work (13), bringing about a balance between their well-being, perceived responsibilities and achievement of organizational values (14).…”
Section: Introductionmentioning
confidence: 99%